A microsimulation model to measure the impact of the economic crisis on household income. Issue 3 (6th June 2016) - Addabbo, Tindara; García-Fernández, Rosa María; Llorca-Rodríguez, Carmen María; Maccagnan, Anna
Abstract : Purpose: – The current economic crisis has significantly increased unemployment, showing higher persistence than expected. However, since microdata from household surveys are issued with delay, they do not allow a prompt analysis of the impact of the economic cycle on households' living conditions. The purpose of this paper is to propose a microsimulation methodology to achieve an evaluation of the impact of economic shocks in terms of household's living conditions to guide policy makers. Design/methodology/approach: – The microsimulation technique developed in this paper is based on a nowcasting approach by using different sources of data and by taking into account a whole set of potential transitions across the different statuses of the labour market and the related changes in income. To validate this microsimulation method, the authors apply it to Italy, a country that has been deeply affected by the crisis. Findings: – Data have been drawn from the European Statistics on Income and Living Conditions Survey for Italy (IT SILC) and from the Labour Force Survey for Italy. The latter data allow us to take into account the changes in the labour market status of individuals due to economic shocks. The validation results support the capability of the model to simulate the effect of the cycle before actual data on income are available. Social implications: – The results obtained would encourage the use of the suggested methodology to anticipate the effect of the economic cycle on household's income therefore enabling the design of effective policies to sustain household income with positive practical and social implications. Originality/value: – Distinct from other microsimulation techniques the methodology proposed in this paper allows us to take into account behavioural effects and the change in the composition of employment and unemployment. Moreover, the authors contribute to the existing literature by considering a whole set of transitions across different labour market statuses and the related changes in income.